Analisis Pengaruh Transportasi Online terhadap Kesempatan Kerja dan Kesejahteraan di Kota Medan - Ian Alfian Ian Alfian; Eka Purnama Sari; Talia Yuedrika (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2019)
This study aims to determine the influence of online transportation on employment opportunities and welfare in Medan City. The method used is a quantitative approach based on the path analysis with a simple linear regression analysis model. The results of the study showed that around 64,9% variables of online transportation explained by changes in variables of employment opportunities and welfare in in Medan City, while the test 35,1% is explained by other factors. About 33,4% of the variables of online transportation affected by employment opportunities and around 31.5% of the online transportation variables aff ected the welfare variable. The significance of the indirect test results indicates that there was an indirect effect of the variable online transportation on welfare through employment opportunities signifi cantly. The impact of this study is there is a significant influence on employment opportunities and community welfare in in Medan City with an Online Motorcycle taxi that can absorb labor and increase the income of UMKM through various services available in the online motorcycle taxi application.